Tasarsız Kavramsal Radyo Ağları İçin Yeni Bir Tümegönderim Yöntemi - Ertuğrul, Orçun (Fen Bilimleri Enstitüsü, 2013)
Mobil teknolojilerin gelişmesiyle ve iletişim ihtiyaçlarının artmasıyla birlikte taşınabilir cihazların kullanımında büyük artış oldu. Taşınabilir cihazların iletişim ihtiyaçlarının karşılanması için doğal olarak telsiz iletişim teknolojilerinin kullanımı yaygınlaştı. Hali hazırda telsiz iletişimi için kullanılan radyo frekansları belirli kurumlara veya belirli işlere rezerve edilmiş durumdadır. Telsiz iletişim teknolojileri yaygınlaşmadan önce birçok frekans aralığının ataması çoktan yapılmıştır. Dolayısıyla gelişen teknolojiler için yeteri kadar frekans aralığı kalmamıştır ve ataması yapılan frekanslar ise verimli bir şekilde kullanılamamaktadır. Yeni kullanım için frekans aralığının olmaması, atanan frekansların verimli bir şekilde kullanılmaması kavramsal radyo kavramının doğmamasına sebep olmuştur. Kavramsal radyolar çalıştıkları frekansı değiştirerek radyo kanallarını dinamik olarak kullanma yeteneğine sahiptirler. Yalnız kanalları kullanırken kanalların sahibi lisanslı kullanıcılara verdikleri zararı belirli bir seviyede tutmaları gerekmektedir. Buna göre kavramsal radyolar kanal boş olduğu sürece o kanalı kullanabilirler, kanalın lisanslı sahibi geldiğinde kullanmak için başka boş bir kanala geçerler. Kanalın lisanslı kullanıcılarına birincil kullanıcı, lisansız olarak kanal boşken kullanan kullanıcılara ise ikincil kullanıcı denir. Kavramsal radyolar normal radyoların kullanıldığı bütün alanlarda kullanılabilirler. Bunlardan bir tanesi de tasarsız ağlardır. Geleneksel tasarsız ağlarda tüme gönderim yöntemi hakkında hali hazırda birçok çalışma bulunmaktadır. Kavramsal radyoların geleneksel radyolara göre çeşitli zorlukları olduğundan tümegönderim yöntemi de geleneksel tasarsız ağlardan farklı olmalıdır. Kavramsal radyoların birbirleriyle haberleşmeleri için boş bir kanal bulmaları ve bu kanalda buluşmaları gerekmektedir. Ayrıca birincil kullanıcılar kavramsal radyoların iletişimine zarar vermektedirler. Bu tür zorluklardan dolayı tümegönderilen mesajın bütün düğümlere ulaşma başarısı düşmektedir. Tümegönderim işleminin birincil önceliği bütün düğümlere iletilmesi istenen mesajın ulaştırılmasıdır. Bundan dolayı çalışmamızda öncelikle bütün düğümlere ulaşmayı hedefledik. Bu hedefin yanında yaratılan tümegönderim maliyetinin düşürülmesi, bütün düğümlere yayılma zamanının azaltılması hedeflendi. Kavramsal radyo tasarsız ağlarında tümegönderim işlemi hakkında literatürde iki tane çalışma vardır. Çalışmalarda düğümler birbirlerine bir kanal setinden bağlıdır ve ortak bir kontrol kanalı bulunmamaktadır. Çalışmaların ilkinde bir düğüm, tümegönderim mesajını komşularına erişebildiği en düşük kanal seti üzerinden komşularına göndermektedir. Birkaç kanal üzerinden gönderim yapıldığından maliyet ve mesajın yayılma süresi artmaktadır. Ayrıca kanal değiştirme süresi, birincil kullanıcıların iletimlere zarar vermesi hesaba katılmamıştır. İletilmek istenen mesajın bütün düğümlere ulaşıp ulaşmadığı incelenmemiştir. Yapılan diğer çalışmada tümegönderim mesajının en kısa sürede ağa yayılması incelenmiştir. Bu çalışmada düğümlerin kullanabileceği bir algoritma önerilmemiştir; çünkü algoritmanın çalışabilmesi için her düğümün topolojiyi ve diğer düğümlerin hangi gönderimleri yaptıklarını bilmeleri gerekir. Önerilen ilk yöntemdeki problemler bu çalışmada da devam etmektedir. Çalışmamızda önerilen yöntemin uygulanabilmesi için her bir düğümde iki radyo modülü bulunmalıdır. Radyolardan bir tanesi kontrol kanalına atanmalı, diğer radyo modülü ise veri iletişimine ayrılmalıdır. Önerilen yöntem hem kontrol kanalını hem de veri kanalını kullanmaktadır. Yukarıda belirttiğimiz tümegönderim amaçlarına ulaşmak için dört farklı özellik içeren bir yöntem önerdik. Bu özelliklerden ilki gönderim yapmak isteyen düğümün komşularını kontrol kanalı üzerinden boş bir kanala çağırmasıdır. Kanal değiştirme işlemi yapıldıktan sonra düğüm mesajı veri kanalından iletir. İkinci olarak sayaç tabanlı tümegönderim yönteminden yararlanılmıştır. Eğer bir düğüm bir mesajı ne kadar çok kere almışsa, o mesajı iletmesiyle yeni kapsayacağı düğüm sayısı o kadar azdır. Bu bilgiden yola çıkarak bir düğümün ileteceği mesaja sahip olan komşularının sayısı, önceden belirlenen eşik değerin üzerinde ise o mesajı düğüm iletmez. Bu mesaj yerine iletme maliyeti çok daha düşük bir kontrol paketi ile komşularını mesaja sahip olduğu hakkında bilgilendirir. Kullanılan bir diğer yöntem ise tümegönderilen mesajı alamayan ve mesajdan haberdar düğümün alamadığı mesajı komşusundan istemesidir. Bir düğüm tümegönderim mesajını almak üzere kanal değiştirip mesajı almayı beklerken çakışmalardan dolayı mesajı alamayabilir veya komşusundan mesajın varlığına dair bir kontrol mesajı almış olabilir. Düğüm öncelikle mesajın diğer komşularından gelmesini belirli bir süre bekler. Eğer mesajı bu süre içinde alamazsa mesaja sahip olduğunu bildiği bir komşusundan mesajı ister. Kullanılan son yöntem ise birincil kullanıcı farkındalığıdır. Boş kanallardan bazıları diğerlerine göre daha iyidir. Birincil kullanıcıların istatistiksel bilgilerinin kullanılmasıyla daha iyi kanalları seçebilmektedir. Böylelikle birincil kullanıcıların iletişime zarar verme ihtimalleri düşürülmektedir. Yukarıda önerdiğimiz yöntemi simülasyon ortamında test ettik. Simülasyon sonuçları hedeflediğimiz gibi düğümlere ulaşmada %100’e çok yakın başarı sağlandığını gösterdi. Düğümlerin hepsine ulaşmanın yanında maliyette azalma, mesajım ağa yayılma süresinde azalma sağlandı.

Rapid development in wireless technologies and demand on being mobile makes big progress in wireless devices. These mobile devices naturally use wireless communication technologies and need empty spectrums to communicate. In current spectrum management design, spectrums are licensed for a specified job or to a specific organization. There are not sufficient spectrum bands for new communication needs. In addition, the assigned spectrums are not utilized most of time. As a result, there is spectrum scarcity problem in wireless world while some of spectrums are underutilized. Cognitive radio (CR) is the most promising technology to overcome these problems. Because of this spectrum scarcity, cognitive radio ad hoc networks (CRAHNs) will take place of conventional ad hoc networks. Cognitive radios can change their transmitter parameters automatically and utilize idle channels dynamically. While unlicensed users (secondary users) are using licensed channels, secondary users should keep damage to licensed users (primary users (PUs)) under a predefined threshold level. According to these, cognitive radio must sense idle channels, can change its transmitter parameters and must sense any collisions between PUs. Broadcasting which means distributing a message from one source node to all nodes in the network is a fundamental operation for ad hoc networks. For example, dissemination of control messages is necessary for path establishment in most ad hoc routing protocols. However, broadcasting is not limited with control messages; broadcasting of alarm signals, code update messages, sensor messages, updating and initializing topology messages are extra necessities. Broadcasting of alarm signals are frequently used in vehicular ad hoc networks. Furthermore, in a disaster or military area, there will be many messages must be broadcasted that may contain large files as pictures, maps or list of something like people or tools. Broadcasting can be also an option when the multicasting is not supported in a network. Broadcasting in CRAHNs has extra challenges than conventional ad hoc networks. As CRs change their transmission channel to occupy idle spaces in the spectrums, rendezvousing of CRs in the same channel must be ensured to broadcast a message in CRAHNs. Furthermore, primary user activities can damage transmission between CRs, which prevent dissemination of broadcast messages in the network and decreases reachability of message. In our study, we offer an algorithm for broadcasting in CRAHNs that maximizes reachability of message, reduces redundancy and propagation delay. In most of CRAHNs, there is a control channel (CC), which can be considered to disseminate messages. However, dissemination of all broadcast messages over the common control channel (CCC) will cause congestion in this channel. Such a bottleneck in the CC cannot be tolerated as it will block all communication, because control messages for connection establishment and spectrum management are all transmitted over that channel. To the best of our knowledge in the literature, there are two studies on broadcasting at cognitive radio ad hoc networks. In the proposed systems two neighbor nodes are connected over a channel subset of all channel set. A node selects a group of channels that access all its neighbors in order to send the broadcast message. Sending message from several channels increases dramatically the cost and the time of dissemination of the broadcast message in the all network. The proposed systems have also no CC, although most of CRAHNs have. The studies do not consider the cost of gathering several nodes in the same channel without CC. In addition, the time cost of channel changing is not taken into account. PUs’ affects are also ignored, reachability of the broadcast message is not mentioned. In our system, a cognitive node has two radio modules. One radio module is dedicated to control channel and the other one is used for data transmission. We can divide our proposed algorithm into four main properties. Firstly, a node that has a broadcast message must gather its neighbors in the same channel by sending a control packet which is sent over control channel. Secondly, the algorithm uses a counter based mechanism to avoid transmission of unnecessary broadcasting messages. When a node’s most of neighbors already have the broadcast message, the number of new covered nodes by its rebroadcast reduces. So that when a node is informed that its most of neighbors have the message, it only sends a tiny control message over control channel to inform its neighbors that it has the message. Thirdly, algorithm gives the opportunity to nodes to request an expected broadcast message if this message is lost. The last property is primary user awareness. CRs can select better channel according to PUs statistical information. This increases successful transmission rate. The proposed algorithm will be explained briefly in this paragraph. When a source node has a broadcast message with the identifier of MSGid (BroadCasMsg(MSGid)) that must be disseminated throughout the network; it calls its neighbors to a proper licensed data channel (Chi) that is used by PUs rarely. It sends the control message CallToChannel(Chi,MSGid) over the CC and changes its channel to Chi. Then the broadcast message is transmitted over the selected channel. A received node of the broadcast message waits until random access delay passes instead of retransmitting the broadcast message immediately. When a relay node is notified for the first time about existence of a broadcast message (MSGid) by a neighbor, it assigns a counter to this broadcast message (counter(MSGid)) and increments this counter each time when it receives other notifications about the same message. If the value of the counter(MSGid) does not exceed a predefined threshold (T) value at the end of random access delay, the relay node calls its neighbors to a proper licensed data by sending the control message CallToChannel(Ch,MSGid) over the CC. If the threshold value of the counter is exceeded, the node does not retransmit the message to avoid redundant transfers, instead it only informs its neighbors that it has the broadcast message by sending the control message HaveMsg(MSGid) over the CC. When a node does not receive the broadcast message after it has been informed by CallToChannel or HaveMsg packets, it requests this broadcast message by sending the control message ReqForMsg(MSGid) to the node which informed it lastly. To evaluate the performance of the proposed scheme, simulation scenarios in different topologies under different PU activities are performed. The result shows that the mechanisms included in the proposed protocol increase the reachability of the messages up to 100%, reduce the overhead in the network and the dissemination time.
An Efficient Broadcasting Scheme For Cognitive Radio Ad Hoc Networks
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2012
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2012
Keywords: Kavramsal Radyo Ağları; Tümegönderim; Birincil Kullanıcı Etkisi; Cognitive Radio Networks; Broadcasting; Primary User Activity